Suplementasi Tepung Daun Kelor (Moringa oleifera) pada Pakan Terhadap Kadar Glukosa Darah dan Total Protein Plasma Kambing Peranakan Boer - Sirat, M M P; Ermawati, R; Alfaruq, F F; Setio, S; Qisthon, A (Politeknik Negeri Lampung, 2025)
Moringa leaves have been used as animal feed to improve ration efficiency, growth performance, reproductive performance, meat and milk production. Moringa leaves contain antioxidant compounds (phenolics and flavonoids) that can reduce oxidative stress. This study aims to determine the effectiveness of adding Moringa oleifera leaf powder to Boer crossbreed goat feed on blood glucose levels and total plasma protein. The study was conducted in June-November 2024 at the PERKASA Boer Goat Group Cattle Pen. The study was conducted experimentally using the Randomized Block Design method with three treatments and three replications. The ration treatments consisted of P0: Basal ration (60% DM cassava leaf silage + 40% DM concentrate); P1: P0 + 5% Moringa oleifera leaf powder from the DM requirement of cassava leaf silage; P2: P0 + 10% Moringa oleifera leaf powder from the DM requirement of cassava leaf silage. The variables in this study were blood glucose levels and total plasma protein of Boer Crossbred goats. Data were analyzed descriptively. The results of this study showed that blood glucose levels in the three treatments were still within the normal range but there was a tendency to increase, namely P0 49.60 mg/dL, in P1 53.60 mg/dL, and P2 45.20 mg/dL; while total plasma protein increased in all three treatments, namely P0 7.42 mg/dL, P1 7.60 mg/dL, and P2 7.24 mg/dL. The conclusion of the research results obtained the best dose of Moringa oleifera leaf powder supplementation in Boer Crossbred goat feed can maintain blood glucose levels within the normal range and increase total plasma protein with the best treatment dose of 95% basal ration + 5% Moringa oleifera leaf powder.